Pertunjukan Seni Talawengkar sebagai Atraksi Seni Budaya di Desa Sitiwinangun Kabupaten Cirebon - Turyati Turyati; Nani Sriwardani (LP2M ISBI Bandung, 2020)
ABSTRACTPottery is a tool or device made of clay and is usually used in everyday life. Pottery is one of the works that was born from the past and still survives today. In the past, pottery was a container for storing crops, foodstuffs, and other consumables. Apart from having functional and historical value, the pottery also has aesthetic value. This pottery is the inspiration for the creation of Talawengkar performance art. Talawengker is defined as shards of pottery, from which the fragments are reused as a medium for children’s play. The object of study is in Sitiwinangun because this area is a location for pottery handicrafts. This article describes the collaborative creative process in research participatory action research. The purpose of creating this artwork is an effort to empower the people of Sitiwinangun Village. The results of the research are in the form of works of art through the Talawengkar performance art attraction pattern using floor patterns and dynamic motion.Keywords: Talawengkar Performance, Pottery, Attractions, Cultural ArtsABSTRAKGerabah merupakan alat atau perangkat yang terbuat dari tanah liat dan biasanya digunakan di kehidupan sehari-hari. Gerabah salah satu karya yang lahir dari masa lalu dan masih bertahan sampai sekarang. Di masa lampau, gerabah merupakan perabotan wadah penyimpanan hasil tanam, bahan makanan, hingga barang pakai lainnya. Selain memiliki nilai fungsi dan sejarah, gerabah juga memiliki nilai estetika. Gerabah inilah yang menjadi latar belakang inspirasi sebagai penciptaan seni pertunjukan Talawengkar. Talawengker diartikan sebagai pecahanpecahan gerabah, dari pecahan itulah yang dimanfaatkan kembali menjadi media permainan anak. Objek studi berada di Sitiwinangun, karena daerah ini merupakan lokasi kerajinan gerabah. Artikel ini memaparkan proses kreatif kolaboratif dalam penelitian participation action reseach. Tujuan penciptaan karya seni ini adalah sebagai upaya pemberdayaan masyarakat Desa Sitiwinangun. Hasil penelitian berupa karya seni melalui pola atraksi seni pertunjukan Talawengkar mengunakan pola lantai dan gerak dinamis.Kata kunci: Pertunjukan Talawengkar, Gerabah, Atraksi, Seni Budaya